Entropy Generation Due to Magneto-Convection of a Hybrid Nanofluid in the Presence of a Wavy Conducting Wall - Geridonmez, Bengisen Pekmen; Öztop, Hakan Fehmi (Mdpi, 2022)
The two-dimensional, time-independent conjugate natural convection flow and entropy generation are numerically investigated in three different cases of a wavy conducting solid block attached to the left wall of a square cavity. A hybrid nanofluid with titania (TiO2) and copper (Cu) nanoparticles and base fluid water in the fluid part is considered in the presence of a uniform inclined magnetic field. The leftmost wall of the cavity is the hot one and the rightmost one is the cold one. Radial-basis-function-based finite difference (RBF-FD) is performed on an appropriate designed grid distribution. Numerical results in view of streamlines and isotherms, as well as average Nusselt number in an interface and total entropy generation are presented. The related parameters such as Hartmann number, Rayleigh number, conductivity ratio, amplitude in wavy wall, number of waviness, and inclination angle of magnetic field are observed. Convective heat transfer in the fluid part is an increasing function of kr,Ra,gamma, while it deflates with the rise in Ha in each case. Total entropy generation increases with the increase in Ra and kr but it decreases with Ha values. Average Bejan number ascends with the rise in Ha and descends with the rise in Ra.
Keywords: wavy conducting solid; conjugate natural convection flow; Cu-TiO2/water; radial basis functions; entropy generation